Sustaining livelihoods or saving lives?: economic system justification in the time of COVID-19 - Jain, Shalini Sarin (Journal of business ethics, 2023)
An ongoing debate in the United States relating to COVID-19 features the purported tension between containing the coronavirus to save lives or opening the economy to sustain livelihoods, with ethical overtones on both sides. Proponents of opening the economy argue that sustaining livelihoods should be prioritized over virus containment, with ethicists asking, "What about the risk to human life?" Defendants of restricting the spread of the virus endorse saving lives through virus containment but contend with the ethical concern "What about people's livelihoods and individual freedoms?" A commonly held belief is that political ideology drives these differential preferences: liberals are more focused on saving lives, whereas conservatives favor sustaining livelihoods with no additional government intervention in the free-market economy. We examine these lay beliefs among US residents in four studies and find that economic system justification (ESJ), an ideology that defends the prevailing economic system when under threat, is a reliable psychological predictor beyond political ideology. Specifically, compared to those who scored low on ESJ, people who scored high on ESJ judged China as more justified in downplaying the spread of virus to protect its interest in the global free-market economy, supported in-person over online learning, viewed shelter in place as less desirable, and perceived the opening of the Texas economy as more legitimate. We also find that multiple psychological mechanisms might be at work-resistance to market interventions, perceived legitimacy of opening the economy, perceived seriousness of the health crisis, and violation of human rights.